Employment Research and State Traditions: A Comparative History of Britain, Germany and the United States - Gauthier, Carol-Anne (Relations industrielles / Industrial Relations, 2009)
Employment Research and State Traditions: A Comparative History of Britain, Germany and the US, by Carola M. Frege, is reviewed.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Collective bargaining; Comparative analysis; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social sciences